Development of heavyweight high performance fiber reinforced cementitious composites (HPFRCC) - Part II: X-ray and gamma radiation shielding properties - Tufekci, M. Mansur; Gokce, Ahmet (ELSEVIER SCI LTD, 2018)
The radiation shielding properties have been investigated for heavyweight high performance fiber reinforced cementitious composites (HPFRCC) produced with silica sand-quartz powder blend, granulated ferrous waste or barite as fine aggregate. The study also dealt with the effects of water-binder ratio (aggregate concentration), curing regime and steel fiber volume fraction on the radiation attenuation coefficient. Linear (mu) and total mass attenuation coefficients (pip), half-value layer (HVL) and tenth value layer (TVL) were determined at photon energies of 0.2 MeV, 0.662 MeV and 1.25 MeV. The total mass attenuation coefficients (pip) were also calculated using XCOM computer code for the novel shielding cementitious composites. The results showed that it is possible to produce HPFRCC with dry unit weight greater than 3745 kg/m(3) and compressive strength of 190 MPa by utilizing granulated ferrous waste as fine aggregate. HPFRCC incorporating barite as fine aggregate enhances the shielding efficiency against 0.2 MeV, whereas using granulated ferrous waste as fine aggregate leads better performance for the attenuation of photons at energies of 0.662 MeV and 1.25 MeV. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: High performance fiber reinforced cementitious concrete (HPFRCC); Heavyweight aggregate; Granulated ferrous waste; Barite sand; X-ray and gamma-ray shielding; Linear attenuation coefficient (mu); Radioactive waste storage; ATTENUATION COEFFICIENTS; CONCRETE; BARITE; SERPENTINE; CODE; LEAD; Construction & Building Technology; Engineering; Materials Science